Aquatic macroinvertebrates in an altitudinal gradient of the Garagoa river, eastern Andes of Colombia - Barrera-Herrera, July Andrea; Díaz-Rojas, Camila Andrea; Prat, Narcís; Roa-Fuentes, Camilo Andrés (Revista de Biología Tropical, 2023)
Introduction: The taxonomic identification of aquatic macroinvertebrates allows characterizing biodiversity in aquatic ecosystems, but in many cases some groups (e.g. Diptera) are not classified to the same taxonomic level than other due to difficulties and poor knowledge on these groups. It becomes relevant in regions little studied and affected by anthropic pressures, such as the Garagoa River in the department of Boyacá, Colombia. Objective: To study the biodiversity of aquatic macroinvertebrates from Garagoa river at the lowest taxonomical level possible in an altitudinal gradient. Methods: From March to June 2021, samples were taken at 40 sites in an altitudinal gradient between 500 and 2 887 m.a.s.l., performing a stratified aleatory sampling (36 Surber nets per site). Results: A total of 70 taxa were reported, however, using a rarefaction technique, the estimated richness for the Garagoa River may be greater than 104 taxa. The orders with the largest number of taxa were: Diptera, Coleoptera, Trichoptera and Ephemeroptera with Chironomidae, Elmidae and Baetidae being the families with the richest genera. Several genera have a wide distribution along the Garagoa River as Simulium, Parachironomus, Cardiocladius, Leptonema, Heterelmis, Neoelmis and Baetodes. The phi-IndVal analysis allowed us to select representative taxa at different altitudes. Thus, Lepthyphes and Belostoma are common with relatively low altitudes, while Culoptila, Lumbriculus and Physa are representative of intermediate altitudes. Finally, Gundlachia, Dugesia and Pentaneura were exclusive and frequent at the higher altitude sites. Conclusions: The composition of the aquatic macroinvertebrate community presented notable differences with respect to the evaluated altitudinal gradient that contrasted with the expected biodiversity patterns. The importance of including taxa that are not generally reported in biodiversity studies is highlighted to better understand the distribution patterns of aquatic communities in Andean streams.